Paranasal Rosai-Dorfman Disease with Osseous Destruction - Kevin Hur; Changxing Liu; Jeffrey A. Koempel (Case Reports in Otolaryngology)
Rosai-Dorfman disease is a rare histiocytic proliferative disorder of unknown etiology typically characterized by cervical lymphadenopathy. Extranodal involvement often manifests in the head and neck region. We present a 10-year-old male who presented to our hospital with left epiphora from an aggressive paranasal mass invading the left orbit with osseous destruction. The mass was surgically biopsied and debulked with histopathological examination revealing Rosai-Dorfman disease. Although rarely found in the sinuses, Rosai-Dorfman disease should be considered when evaluating sinonasal masses.